Cara supervisi yang efektif untuk meningkatkan kinerja petugas puskesmas dalam pelayanan imunisasi di Kabupaten Agam Propinsi Sumatera Barat = Effective supervision for improving staff performance at ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Background: This Study was aimed at finding out an effective supervision for improving performance of immunization service staff at the community health centers in Agam regency, West Sumatera. The immunization service program still faced problems, i.e.low target, high number of immunization failure, and the number of diseases prevented using immunization services staff, although efforts had been made for quality assurance. One among many efforts to improve staff performance in immunization service was done by supervision. This method however was still not effective in improving staff performance. Methods: This was a quasy-experimental study using Pre and Post Test Non Equivalent Control Group Design. The location of the study was decided through inclusion criteria and matching in which the subjects were staff of immunization service at the community health centers. The subjects were divided into three intervention groups of supervision, they were: 1) group of community health center 'A' (self-assessment supervision)